2015
DOI: 10.1002/lary.25250
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and cause of readmissions following pediatric otolaryngologic surgery

Abstract: Readmissions after pediatric otolaryngologic surgery are relatively uncommon. These readmission rates vary directly with the type of procedure performed, as well as patient level factors (i.e., patient age, ethnicity, and the presence of other medical comorbidities). These data demonstrate that if readmission rates are to be used as a quality measure in pediatric otolaryngology procedures, complex risk adjustment of patient level variables will be necessary to accurately compare outcomes between different hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…In general, patients with longer LOS at index admission were found in seven studies to be at greater risk of readmission following surgical procedures (OR=1.01 to 13.96)72 79 81 82 86 90 although one study87 found shorter than 3 days of hospitalisation at the index admission was a risk factor for patients who underwent spinal fusion (OR=1.89).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, patients with longer LOS at index admission were found in seven studies to be at greater risk of readmission following surgical procedures (OR=1.01 to 13.96)72 79 81 82 86 90 although one study87 found shorter than 3 days of hospitalisation at the index admission was a risk factor for patients who underwent spinal fusion (OR=1.89).…”
Section: Resultsmentioning
confidence: 99%
“…Age at index admission or surgery72 77 78 82 85 90 and the ASA class71 75 80 83 84 89 were cited in six differing studies. Age, however, was inconsistent across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 For condition-specific unplanned readmissions, prevalence ranges from 19% to 31% for mental health conditions based on 12-month measurements, [16][17][18][19] from 4.5% to 38% for respiratory diseases based on 28-day to 1-year measurements [20][21][22][23][24][25] and from 0.3% to 27.8% for general surgeries based on 7-day to 1-year measurements. [26][27][28][29][30][31][32][33][34] There is limited published literature measuring all-cause paediatric unplanned hospital readmissions in Australia. Five Australian studies were identified with a focus on specific health condition-associated readmissions; these studies examined readmissions across mental health conditions, 16 asthma, 24,25 term live-born infants 35 and paediatric intensive care patients.…”
Section: Introductionmentioning
confidence: 99%